2023
DOI: 10.3847/1538-4357/acf845
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Angle-dependent Partial Frequency Redistribution on the Scattering Polarization of the Solar Na i D Lines

Gioele Janett,
Ernest Alsina Ballester,
Luca Belluzzi
et al.

Abstract: The long-standing paradox of the linear polarization signal of the Na i D1 line was recently resolved by accounting for the atom’s hyperfine structure and the detailed spectral structure of the incident radiation field. That modeling relied on the simplifying angle-averaged (AA) approximation for partial frequency redistribution (PRD) in scattering, which potentially neglects important angle–frequency couplings. This work aims at evaluating the suitability of a PRD-AA modeling for the D1 and D2 lines through c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(64 reference statements)
0
1
1
Order By: Relevance
“…We find a good agreement between the two calculations, which highlights the suitability of the AA approximation for modeling the linear polarization pattern of the Ba II D 1 line, at least in the absence of magnetic fields. This contrasts with the results of the analogous investigation for the Na I D 1 line reported in Janett et al (2023), in which that approximation was found to have a clear impact on the shape of the Q/I profile. Although it is not shown here, we were able to reproduce such findings in the nonmagnetic case using HanleRT.…”
Section: The Impact Of the 5d Metastable Levels In The Zerofield Casecontrasting
confidence: 99%
See 1 more Smart Citation
“…We find a good agreement between the two calculations, which highlights the suitability of the AA approximation for modeling the linear polarization pattern of the Ba II D 1 line, at least in the absence of magnetic fields. This contrasts with the results of the analogous investigation for the Na I D 1 line reported in Janett et al (2023), in which that approximation was found to have a clear impact on the shape of the Q/I profile. Although it is not shown here, we were able to reproduce such findings in the nonmagnetic case using HanleRT.…”
Section: The Impact Of the 5d Metastable Levels In The Zerofield Casecontrasting
confidence: 99%
“…This approach is otherwise correct in the absence of magnetic fields. However, in the presence of magnetic fields, the same substitution leads to an incorrect expression of the magnetic Hamiltonian (e.g., Janett et al 2023). Thus, the calculations with HanleRT presented in this work are restricted to the nonmagnetic case.…”
Section: The Impact Of the 5d Metastable Levels In The Zerofield Casementioning
confidence: 99%